(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Flownets, geo-electric layers construction and groundwater exploration analysis was investigated in the eastern and Western parts of Ilorin of Southwestern Nigeria. Apata-Yakuba, Eleko-yangan, Tepatan, Oke-Andi at the Eastern part and Akamo, Idi-Araba in the Western part of Ilorin were surveyed to depict the exact locations for potential future groundwater exploration. A preliminary step to collect lithologs of wells from the records of Nigeria Hydrological Services Agency used 35 water samples taken from hand dug wells and boreholes. Static water levels, total depth and coordinates of hand dug wells were measured using tape and GPS respectively. The Static water level (below ground surface and above sea level) values and their coordinates were processed using IPWIN resist software to generate the water level locations on topographical contour maps and the groundwater flow net of the study area. Result reflects the presence of crystalline rocks consisting of migmatite gneiss, granite gneiss, quartzite and granite. Analysis and interpretation of flownet shows ascending equipotential lines at the Eastern part indicating an easy groundwater movement, and divergent equipotential lines at the Western part indicating difficulty in water movement in the study area. The static water levels values together with the corresponding coordinates were superimposed on the geological map of the study area. This research reveals the water table is very close to ground surface in Oyun, Oke-Andi resulting into digging of shallow wells by the dwellers of the area. Water table is also far away from the surface in places Tepatan, Apata-Yakuba among others